2009
DOI: 10.4049/jimmunol.0901361
|View full text |Cite
|
Sign up to set email alerts
|

Dicer-Dependent MicroRNA Pathway Controls Invariant NKT Cell Development

Abstract: Invariant NK T (iNKT) cells are a separate lineage of T lymphocytes with innate effector functions. They express an invariant TCR specific for lipids presented by CD1d and their development and effector differentiation rely on a unique gene expression program. We asked whether this program includes microRNAs, small noncoding RNAs that regulate gene expression posttranscriptionally and play a key role in the control of cellular differentiation programs. To this aim, we investigated iNKT cell development in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 37 publications
6
91
0
Order By: Relevance
“…This phenomenon has been linked in particular to the loss of function of miRNA-deficient Tregs, and mice with either a general deficiency of miRNA or selective knockdown of miR-146a in Tregs displayed a fatal autoimmune disease (26)(27)(28)(29)(30). However, miRNA ablation in T cells also results in defects in natural killer T-cell development (31,32) and the differentiation of T-helper cells that may contribute independently to autoimmunity (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been linked in particular to the loss of function of miRNA-deficient Tregs, and mice with either a general deficiency of miRNA or selective knockdown of miR-146a in Tregs displayed a fatal autoimmune disease (26)(27)(28)(29)(30). However, miRNA ablation in T cells also results in defects in natural killer T-cell development (31,32) and the differentiation of T-helper cells that may contribute independently to autoimmunity (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that in their transferring experiments, four to five mice per group may not have enough power to detect a difference for this mild reduction, compared with the almost complete blocking of early iNKT cell development in the mice with miR-150 overexpression. Compared with iNKT cells in bone marrow-or thymus-specific total miRNA deletion mouse models (26)(27)(28), miR-150 deletion alone is unlikely accountable for the profound interruption of iNKT cell development, maturation, and function identified in those mice. This may suggest the potential involvement of multiple miRNAs or groups of miRNAs in iNKT cell developmental and functional regulation, which is also supported by our recent miRNA expression profiles of iNKT cells (Q.H.…”
Section: Discussionmentioning
confidence: 99%
“…Small microRNAs (miRNAs) are short noncoding RNAs (20-23 nt) that negatively regulate gene expression by inducing the degradation or translational repression of the target protein-coding mRNAs (25). Recently, our laboratory and another group found that deletion of Dicer, the RNase III enzyme essential for the processing of mature functional miRNAs, results in a profound interruption of iNKT cell development, maturation, and function (26)(27)(28). However, little insight has been made concerning the role of specific miRNAs in the development and function of iNKT cells.…”
mentioning
confidence: 99%
“…A Dicer dependent miRNA pathway is important in the regulation of invariant NK T cell differentiation, func tion, and homeostasis [53] . The normal granulocytic differentiation requires the zinc finger protein growth factor independent1, which is a transcription inhibitor that regulates the expression of miR21 and miR 196b during myelopoiesis [54] .…”
Section: Mirnas and Other Kind Of Innate Immune Cellsmentioning
confidence: 99%